Boundaries of Beige - Nazzari, Anna (Anna Nazzari, 2014)
Structures have a tendency to measure, delineate, regulate and mark bodies. In Boundaries of Beige Marzena Topka uses textiles such as office clothing and string in unusual ways to explore organisational structures and how they work their way into our daily lives. Whether this happens through duty, responsibility and necessity, or through self imposed routines and habits the results are not dissimilar. We are surrounded by regulations, procedures, instructions and guidelines that provide us with codes of behavior and define our lives. Drawing from her Eastern European upbringing Topka’s works represent how structures take form and yet maintain an inherent fluidity. The artist questions the supposed rigidity of structure creating large-scale textile forms, which by the nature of the material remain malleable. This exhibition combines installation, film and small-scale sculpture by Topka and includes sound performances by Beige (Adam Burges, Jeremy Cope, Anetta Nevin, Ben Rose and Jerome Turle).